Access to Essential Utilities by The Bottom of The Pyramid (BoP) Population in Colombia (2024)
Objective: The article analyzes whether there is an association between the different levels of the BoP and the area of residence with the variables of access to essential utilities in a region of Colombia. Theoretical Framework: The literature review addresses the concepts of access to essential utilities and the BoP Population. Method: The data analyzed comes from 2,394 homes in the Norte de Santander region (Colombia), which were segmented by poverty conditions, resulting in 1,521 in the BoP. To establish the association between variables, the Mann Whitney U test was used; the magnitude of the association has been determined using Cramér's V coefficients. Results and Discussion: Results show that cooking fuel, excreta disposal, and urban waste management services have a high association with the socioeconomic levels at the BoP; while the drinking water service has a moderate association, yielding a Cramer V value of 0.47. Regarding the area of residence, the independence between the variables Access to essential utilities and Area of residence is rejected; that is, they are associated. Little interest was evident on the part of public and private organizations in the essential services sector in serving this market segment, by not including it in their marketing targeting strategies. The finding was also that people from the BoP in Norte de Santander, Colombia, who reside in urban areas, have better access to these services than those in rural areas, confirming the hypotheses raised based on similar studies carried out in regions from Asia. Research Implications: These results leads to recommending that companies in the essential services sector that have the BoP as their target market make a distinction in marketing strategies between the urban and rural markets of the BoP. Originality/Value: The study uses an innovative socioeconomic level classification method that facilitates comparison with other regions by not using income level as the only variable.